Dosis de cuyaza en las características agronómicas y rendimiento de Brassica oleracea L. repollo variedad fuyutokio, Loreto 2024 - Asturo Patricio, Joel (2025)
The objective of this research was to evaluate the effect of different doses of cuyaza on the agronomic characteristics and yield of *Brassica oleracea* L. cabbage var. Fuyutokio under field conditions in Loreto, Peru. The experiment was conducted using a randomized complete block design (RCBD) with four treatments: 0, 10, 20, and 30 t/ha of cuyaza, and four replicates per treatment. Variables such as plant height, plant width, root length, stem length, number of leaves, leaf weight, total plant weight, head diameter, and head weight were evaluated. The results indicated that the doses of cuyaza had a significant effect on plant height (p < 0.05), root length (p < 0.05), stem length (p < 0.01), leaf weight (p < 0.001), total plant weight (p < 0.001), and head weight (p < 0.001). The doses of 20 and 30 t/ha showed the highest averages for plant height (38.0 and 40.0 cm) and total plant weight (1900.0 g). Likewise, head weight reached its highest value with 30 t/ha (987.0 g). It is concluded that the doses of 20 and 30 t/ha of cuyaza significantly promote vegetative growth and yield of cabbage and are recommended to maximize production in sustainable horticultural systems.